Ferroelectric characteristics of BiFeO3 thin films prepared via a simple chemical solution deposition - Simoes, A. Z.; Gonzalez, A. H. M.; Cavalcante, L. S.; Riccardi, C. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2007)
BiFeO3 (BFO) thin films were fabricated on Pt(111)/Ti/SiO2/Si substrates by using a polymeric precursor solution under appropriate crystallization conditions. The capacitance dependence on voltage is strongly nonlinear, confirming the ferroelectric properties of the films resulting from the domain switching. The leakage current density increases with annealing temperature. The polarization electric field curves could be obtained in BFO films annealed at 500 degrees C, free of secondary phases. X-ray photoelectron spectroscopy spectra of films annealed at 500 degrees C indicated that the oxidation state of Fe was purely 3+, demonstrating that our films possess stable chemical configurations. (c) 2007 American Institute of Physics.